Ajim - A. Louis (Encyclopédie berbère, 1986)
BACKGROUND: In New York City, many Hispanic immigrants work in occupations that are not only higher risk for occupational injury but that also fail to provide health insurance or paid sick leave. This study aimed to identify barriers to accessing both primary care and occupational health care for Hispanic immigrant workers, specifically those in informal job arrangements. METHODS: We conducted a qualitative study that included: (1) focus groups with Hispanic house cleaners, and (2) semi-structured interviews with service providers (clinicians, social workers, and patient coordinators) of two hospital systems and key stakeholders in a community-based organization. RESULTS: Sixteen housecleaners and 11 service providers participated. Identified barriers to primary care included cost of care, no time off from work, difficulties navigating healthcare systems or lack of knowledge regarding the healthcare system, language discordance, and fear related to immigration status. Barriers to occupational healthcare access (including workers' compensation [WC]) were related to the complexity of the WC system, fear of retaliation (including being fired from work), language discordance, and fear related to immigration status. CONCLUSION: Hispanic immigrant workers face many challenges to address their healthcare needs and identified barriers that were not brought up by service providers. Future efforts need to focus on bridging existing primary care and occupational health services to reduce the challenges Hispanic immigrant workers face, and disseminating information on available health resources.